2018
DOI: 10.2147/ott.s186186
|View full text |Cite
|
Sign up to set email alerts
|

Natural product pectolinarigenin inhibits proliferation, induces apoptosis, and causes G2/M phase arrest of HCC via PI3K/AKT/mTOR/ERK signaling pathway

Abstract: BackgroundHepatocellular carcinoma (HCC) is characterized by considerable phenotypic and molecular heterogeneity, but the overall survival of HCC patients remains extremely poor. Thus, novel and efficient alternatives to antitumor agents are urgently needed. Pectolinarigenin, a flavonoid compound extract, has been previously reported for the treatment of nasopharyngeal cancer. However, the potential antitumor roles of pectolinarigenin in HCC have not been clearly elaborated. In the present study, we investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…To examine the detailed mechanisms underlying M2 macrophages' role in regulating HCC cells invasion and migration, we tested the expression of proteins that have been connected with cancer cell invasion and migration [12][13][14][15][16][17][18] in both culture alone and in co-culture. The exploratory experiments led to the focus on MMP9 as the results showed that MMP9 protein expression was increased after co-culture, both in SK-HEP-1 and HA22T HCC cells ( Fig.…”
Section: Mechanism Dissection Of How M2 Macrophages Increase the Hcc mentioning
confidence: 99%
“…To examine the detailed mechanisms underlying M2 macrophages' role in regulating HCC cells invasion and migration, we tested the expression of proteins that have been connected with cancer cell invasion and migration [12][13][14][15][16][17][18] in both culture alone and in co-culture. The exploratory experiments led to the focus on MMP9 as the results showed that MMP9 protein expression was increased after co-culture, both in SK-HEP-1 and HA22T HCC cells ( Fig.…”
Section: Mechanism Dissection Of How M2 Macrophages Increase the Hcc mentioning
confidence: 99%
“…In addition, the PI3K/AKT signalling pathway is also involved in the regulation of tumour progression. A previous study showed that pectolinarigenin suppressed the viability and caused apoptosis of hepatocellular carcinoma cells via the inactivation of PI3K/AKT signalling pathway . Convincing evidence showed that target regulating the PI3K/AKT/mTOR signalling pathway may enhance the radiosensitivity or chemosensitivity of OSCC .…”
Section: Discussionmentioning
confidence: 99%
“…Our data showed that SLBZ-AP Many researchers confirmed that PI3K/Akt/mTOR signaling pathway is related to a few biological activities to affect cell proliferation, survival, and migration [7,8], especially to stimulate proliferation, survival, invasion/metastasis, and metabolic reprogramming and suppress autophagy, which is involved in possible mechanisms of oncogenic transformation [9]. PI3K/Akt/mTOR signaling pathway is commonly activated and suppression of its activation may inhibit cells proliferation and metastasis in cancers of the lung [10,11,50], colorectal [51,52], esophagus [53], breast [54][55][56], liver [57,58], and kidney [59,60], which has been considered a promising therapeutic target. Whether the PI3K/Akt/mTOR signaling pathway involved in SLBZ-AP affects BMLC was further explored in our study, results of which indicated that the mRNA and protein expression of AKT, mTOR, P70S6, and VEGF as well as protein expression of p-AKT, p-mTOR, p-P70S6, and VEGF was significantly increased in the marrow of tibia from BMLC mice.…”
Section: Discussionmentioning
confidence: 99%